(untitled) (Raparin Journal of Humanities (RJH), 2023)
In this study, the role of investigative media in fighting corruption in the Kurdistan Region is examined. In order to show the role of the media in fighting corruption and to determine the degree of corruption, the journalistic reports and investigations of the programs (Bnkoll- investigate ) and (Snduqy Rash- Black box) on Kurdistan 24 and Diplomatic Magazine were investigated The channels are located in the Kurdistan Regional Government (KRG) and, throughout the months of 2021, for all reports on corruption in both fists of the study. This study is a descriptive study, non-analytical methods were used to analyze the content of the research articles, and the analysis is presented in several aspects, namely: identifying the types of corruption and including issues related to each type In the reports received. In the assessment, the researcher mapped the geographical boundaries of the research reports. The results showed that although the research reports worked on identifying issues of corruption, to fight corruption, in the first place working on cases (financial and economic corruption), by (54%), but did not work on political corruption cases. While their main objective was to fight corruption (33.7%), and, in exposing corruption, there are differences in geographical boundaries, so that Sulaimani province has done the most work (37.8%), compared to Erbil province (13). 5%), and the results revealed that they worked to some extent within the characteristics of the research reports.